An improved palm oil refining process - Tan, Chin Ping; Zulkurnain, Musfirah; Lai, Oi Ming (2012)
The present invention relates to a process of refining palm oil in order to produce a refined, bleached and deodorized (RBD) palm oil with reduced level of 3-monochloropropane-1,2-diol (3-MCPD) esters and equivalent RBD palm oil quality for all range of crude palm oil (CPO) feed. Accordingly, the process comprises the steps of water degumming of crude palm oil, removal of aqueous phase by centrifugation, followed by acid degumming at lower temperature. Water degumming removes 3-MCPD esters precursors while controlled acid degumming purifies the crude oil from gums and impurities. The degummed oil is then washed with certain amount of water and the aqueous phase is removed by centrifugation to remove remaining 3-MCPD esters precursors after acid degumming. Subsequently, bleaching is conducted with an activated bleaching earth and silicate adsorbent (for example magnesium silicate, calcium silicate and aluminum silicate) as filter aid and final adsorption of the 3-MCPD esters precursors prior to deodorization step. In this way, the refining process allows production of RBD palm oil with less formation of 3-MCPD esters even from low quality CPO.